Relative impacts of long-term nutrient management practices on nitrogen dynamics in rice (Oryza sativa)-based organic cropping systems of Indo-Gangatic Plains - MEENA, A L; PANDEY, R N; KUMAR, DINESH; SHARMA, V K; DATTA, S P; SINGH, GEETA (The Indian Journal of Agricultural Sciences, 2019)
Limited information is available on the impacts of long-term organic nutrient management practices on different nitrogen pools and urease enzyme activity. Hence, the major objective of this study was to evaluate long-term (12 years) organic nutrient management practices’ impact on different nitrogen pools and urease activity. Treatments were two cropping systems, viz. rice (Oryza sativa L.) –wheat (Triticum aestivum L.)-mungbean [Vigna radiata (L.) Wilczek] (RWMCS) and rice-wheat (RWCS) in strips and seven nutrient combinations, i.e. FYM equivalent to 60kg N/ha, VC equivalent to 60 kg N/ha, FYM + crop residue (CR) of preceding crop @ 3 t/ha for each rice, wheat and mungbean, VC+CR, FYM+CR+BF and VC+CR+BF and control under sub-plots. Available N, microbial biomass N (MBN), mineral N, potential mineralizable (PMN), total N and urease enzyme assay were analysed in 0-15 cm soil depth. Results showed that FYM+CR+BF recorded 5.5% and 7.7% higher available N as compared to the FYM alone in both RWMCS and RWCS, respectively. Similarly, an increment of 4.0% and 7.5% in available N was observed with VC+CR+BF over VC alone in both the cropping systems, respectively. MBN ranged from 47.1 mg/kg (control) to 69.6mg/kg (FYM) under RWMCS and 43.2 mg/kg (control) to 67.6 mg/kg (FYM) under RWCS. Treatments FYM+CR and FYM+CR+BF showed 5.0% and 30% lower ammonical N as compared to FYM alone treatments in RWMCS. Concurrently, in case of RWCS, the magnitude of decrease in ammonical N content was similar (21.1%) both in FYM+CR and FYM+CR+BF. The total mineral nitrogen (NH4+ -N+ NO 3 - -N) content was significantly influenced by the application of organic manures, crop residues and biofertilizers in both RWMCS and RWCS and their interaction effects. The FYM+CR+BF treatment recorded highest (56.4 mg/kg) potential mineralizable N (PMN) among all the treatments with an increment of 86.4% and 104% the over control in RWMCS and RWCS, respectively. The VC+CR showed 6.1% and 5.5% higher total N content over the control in RWMCS and RWCS, respectively. The content of urease enzyme ranged from 155.1 μg urea/g soil/h (control) to 230.4 μg urea/g soil/h (VC+CR) and 144.3 μg urea/g soil/h (control) to 233.6 μg urea/g soil/h (FYM+CR) in RWMCS and RWCS, respectively